Socioeconomic Determinants of Trainees’ Enrolment and Participation in Public TVETS in Nakuru County, Kenya - Mugambi , Mercy M.; Kyalo Makato, Benard; M. Kalai, Jeremiah (International Journal of Scientific Research and Management (IJSRM), 2022)
Technical, Vocational, Education and Training (TVET) focuses on providing lifelong skills that meet the needs of the work place, industry and self-employment. The importance of TVET is in the global agenda for development and refocusing education and training in the 21st Century. Purposely, this study sought to investigate individual and socioeconomic determinants of trainees’ enrolment and participation in public TVETs in Nakuru County, Kenya.  The objective of the study was to establish how socioeconomic status influenced trainees’ enrolment and participation in public TVETs in Nakuru County, Kenya and the research hypothesis that was tested stated that there is no significant relationship between socioeconomic status and trainees’ enrolment and participation in public TVETs in Nakuru County, Kenya. The study employed descriptive survey research design with a sample size 12 TVETs, 30 trainers and 331 trainees drawn from the target population of 24 public TVETs, 150 trainers and 2385 trainees from entire Nakuru County. Data collection instruments were interview guide, questionnaires and document analysis guides. Data was analysed qualitatively and quantitatively. Descriptive statistics which included frequencies percentages, means and standard deviations were generated and used in discussing the research findings. Correlation analysis and one-way analysis of variance (ANOVA) at 95% confidence interval of the difference (ά=0.05) was also done. The findings showed that: there was a significant relationship between socioeconomic status and trainees’ enrolment; there was a statistically significant mean difference between socioeconomic status and trainees’ enrolment in public TVETs; there was statistically significant mean difference between income of parents, level of education of parents and occupation of parents and trainees’ enrolment in TVETs. The findings of the correlation between socioeconomic status of trainees and enrolment in TVETs showed that, P value = .002< P= 0.05, HO2 was rejected and the conclusion was that there was a significant relationship between socioeconomic status of trainees and enrolment of trainees. The analysis led to the conclusion that, socioeconomic status determined enrolment in TVETs.